The Effect Of Anthropomorphic Appeal On Consumer Protective Behavior In Service Facilities - Dwinita Laksmidewi (Jurnal Manajemen, 2022)
Implementing health protocols, wearing masks, and maintaining physical distance in the service facilities are necessary during this Covid-19 pandemic. So, we need a health appeal message in the service industry to discipline consumer behaviour. This study examines the effects of anthropomorphic persuasive appeal on consumer protective behavior. This study consists of two studies and used an experimental method. The results showed that the anthropomorphic persuasive message made consumers feel more fear, understand the message more easily, and perceive that the object had more power. The effect of messages on protective behavior is significantly mediated by fear. Meanwhile, ease of understanding and power are not significant mediations. Study 2 which focuses on the application in service facilities also shows that anthropomorphic appeal can influence protective behaviour. These results indicate that the emotional aspect, in this case, the fear of consumers, has more influence on protective behaviour.